Large size lenticular shaped phosphors-in-glass by Isobam-APS gel casting to act for converting and condensing in LCD projector. Issue 5 (1st March 2023) - Tian, Junjie; Liu, Hongmei; Guo, Rong; Sun, Honghao; Chen, Yufeng; Wang, Yi; Xu, Qian; Zhu, Yao; Yao, Qing
Abstract: White light diodes (WLEDs) composed of blue chip and phosphor-converter are widely used in liquid crystal display (LCD) projectors as backlights. And it often needs a condenser lens to irradiate white light onto the LCD screen. In this paper, a large size lenticular shaped phosphors-in-glass (PiG) was prepared by Isobam-APS gel casting for the first time. The PiG could act for converting and condensing in LCD projector. Then a rectangular light spot similar to the shape of LCD screen was obtained to reduce the loss of light. The maximum temperatures of the chip and PiG were 62.1 °C and 57.3 °C respectively after working for 600 s and gradually stabilized by simulation. It was proved that simulation result was reliable through comparing with the actual measured value and the lenticular shaped PiG had good heat dissipation capacity for its large area. In conclusion, this is a successful application of PiG in LCD projector, which has guidance and promoting effect.